Lack of Clinical Relevance of ANA and ASMA Positivity in Patients with Liver Transplantation without a History of Autoimmune Diseases. (27th February 2017) - Pellegrini, Lucienne; Parrilli, Gianpaolo; Santonicola, Antonella; Cinquanta, Luigi; Caputo, Cesare; Ciacci, Carolina; Zingone, Fabiana
Abstract : The relevance of isolated autoimmunity elevation in orthotopic liver transplantation (OLT) patients is unknown. Our aim was to analyse how serum autoantibodies change in time and to evaluate their clinical relevance in OLT patients. Patients were invited to provide samples to evaluate ANA, AMA, ASMA, and LKM at the time of enrolment (T 0), after 6 months (T 6), and after 12 months (T 12). We included 114 patients in the study (76% males, median age 62.5 years), finding isolated elevation of at least one serum antibody in up to 80% of them. We described fluctuating positive autoantibodies in the one year of observation, with only 45.6% of patients positive for ANA and less than 2% positive for ASMA, at all three times. Isolated elevation of tissue antibodies was not related to gender, age, HCC at transplant, early rejection, cause of transplantation, immunotherapy taken, and age at the time of the study. We did not detect a higher prevalence of positive autoimmunity in patients with signs of liver injury. ANA and ASMA evaluation in patients with liver transplantation and no history of autoimmune disease has no clinical relevance, since it varies in time and is not related to any risk factors or liver injury. Routine autoimmunity evaluation should be avoided.